1985
DOI: 10.1515/cclm.1985.23.3.157
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Reference Intervals for 10 Serum Proteins Measured by Rate Nephelometry, Taking into Consideration Different Sample Groups and Different Distribution Functions

Abstract: Summary: Reference intervals were established for 10 serum proteins (IgA, IgG, IgM, transferrin, haptoglobin, complement C3, complement C4, otj-acid-glycoprotein, Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 7 publications
0
32
0
Order By: Relevance
“…Gender differences in AAT levels were even present in the situation of severe AAT deficiency although the results were not adjusted for hormone intake [23]. While previous reports on the association between use of oral contraceptives and AAT in the blood exist [24,25], our study extends this association to postmenopausal hormone intake. Our findings are compatible with an effect of estrogens or progesterone on hepatic AAT metabolism, which may be mediated by an inhibition of cytochrome P-450 activities [26].…”
Section: Discussionmentioning
confidence: 54%
“…Gender differences in AAT levels were even present in the situation of severe AAT deficiency although the results were not adjusted for hormone intake [23]. While previous reports on the association between use of oral contraceptives and AAT in the blood exist [24,25], our study extends this association to postmenopausal hormone intake. Our findings are compatible with an effect of estrogens or progesterone on hepatic AAT metabolism, which may be mediated by an inhibition of cytochrome P-450 activities [26].…”
Section: Discussionmentioning
confidence: 54%
“…A total of 109 publications were identified as containing immunoglobulin measurements on healthy individuals (9-117). Thirty-two studies reported only an arithmetic mean and insufficient data to estimate a reliable central estimate (13,18,(21)(22)(23)25,27,29,33,37,39,40,44,45,49,54,55,57,58,62,63,65,67,70,80,86,87,92,93,108,115,117). Twenty-two studies did not state a reference material and/or an assay method and were also excluded (11,12,14 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies did not include the age of the study subjects (16,17,27,29,43), and two had multiple reasons for exclusion (15,33). The remaining 16 studies (4)(5)(6)13,14,19,21,23,24,(30)(31)(32)36,48,51,57) provided acceptable central estimates. Of these, 12 also provided acceptable reference ranges (4)(5)(6)19,21,24,(30)(31)(32)36,48,51).…”
Section: Number Of Studies Available For Analysismentioning
confidence: 99%
“…A total of 27 publications were identified that contained information on α 1 -antitrypsin in apparently healthy individuals (4)(5)(6)8,11,13,17,18,(20)(21)(22)(23)(24)(25)(26)(37)(38)(39)(40)(41)45,49,(51)(52)(53)56,63). Four studies did not include adequate data on a reference material or an assay methodology (8,18,39,49).…”
Section: Number Of Studies Available For Analysismentioning
confidence: 99%
See 1 more Smart Citation